2003
DOI: 10.1080/00365520310004524
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease versus irritable bowel syndrome: a hospital‐based, case‐control study of disease impact on quality of life

Abstract: Our study supports the notion that, at least in referral centres, patients with IBS show health-related quality of life, psychological distress and recent occurrence of stressful life events of severity at least comparable with age-matched IBD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 48 publications
5
77
0
6
Order By: Relevance
“…2 However, only one-third of those who suffer from IBS-like symptoms see a physician, the actual prevalence may be much higher. IBS impairs the quality of life in patients to a similar degree as in patients with inflammatory bowel diseases 3 and the impairment is proportional to the severity of the symptoms experienced by the patient. 4 IBS is a heterogeneous entity with etiology comprising of multiple factors such as inflammation, neuroimmune interactions, 5 gut microbiota, 6 environmental pollution, 7 and abnormal gut-brain axis.…”
Section: Introductionmentioning
confidence: 99%
“…2 However, only one-third of those who suffer from IBS-like symptoms see a physician, the actual prevalence may be much higher. IBS impairs the quality of life in patients to a similar degree as in patients with inflammatory bowel diseases 3 and the impairment is proportional to the severity of the symptoms experienced by the patient. 4 IBS is a heterogeneous entity with etiology comprising of multiple factors such as inflammation, neuroimmune interactions, 5 gut microbiota, 6 environmental pollution, 7 and abnormal gut-brain axis.…”
Section: Introductionmentioning
confidence: 99%
“…An increased stress appears to facilitate disease reactivation. IBDs can be affected by stress 9,10 . Stress modulates colonic motility 11 and it influences the endocrine and immune system which are mediators of the inflammatory process.…”
Section: Stress and Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…IBS and IBDs have significantly greater stress burdens than controls 10 and higher levels of psychiatric distress, alexithymia and somatosensory amplification 14 . Unlike short-term stress, the perception of chronic stress appears to increase the risk of exacerbation of ulcerative colitis 13 .…”
mentioning
confidence: 99%
“…Over 50% of IBS subjects-consulters [33] and non-consulters alike [34] report that stressful events precipitate or worsen their symptoms. While some previous studies have observed that IBS subjects experience a slightly greater number of stressful life events than do controls or patients with other digestive disease [35,36] , other studies have observed no differences in this regard [6,37] . In a prospective study, Levy et al [38] failed to find differences between IBS subjects and controls in the number of positive or negative daily events, but self-reported daily stress was higher among IBS subjects.…”
Section: Discussionmentioning
confidence: 70%